2009
DOI: 10.1017/s1751731108003583
|View full text |Cite
|
Sign up to set email alerts
|

Competing risk analyses of longevity in Duroc sows with a special emphasis on leg conformation

Abstract: A competing risk approach was used to evaluate the influence of several factors on culling risk for 587 Duroc sows. Three different analyses were performed according to whether sow failure was due to death during productive life (DE) or to one of two causes for voluntary culling: low productivity (LP) and low fertility (LF). Sow survival was analyzed by the Cox model. Year at first farrowing (batch effect) significantly affected sow survival in all three analyses ( P , 0.05 for DE and P , 0.001 for LP and LF) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 33 publications
(49 reference statements)
0
2
0
Order By: Relevance
“…Heritabilities for hoof growth ranged from 0.24–0.27 in Landrace and from 0.36–0.38 in Large White sow populations [ 23 , 24 ]. Of importance was also the fact that abnormal hoof growth reduced survivability in Duroc [ 4 , 5 ] and Landrace sows [ 4 ]. Recently Johnson et al [ 2 ] showed that the lateral toes in Yorkshire sows were growing slower than the lateral toes in Duroc and Crossbred (Duroc × Yorkshire) sows.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Heritabilities for hoof growth ranged from 0.24–0.27 in Landrace and from 0.36–0.38 in Large White sow populations [ 23 , 24 ]. Of importance was also the fact that abnormal hoof growth reduced survivability in Duroc [ 4 , 5 ] and Landrace sows [ 4 ]. Recently Johnson et al [ 2 ] showed that the lateral toes in Yorkshire sows were growing slower than the lateral toes in Duroc and Crossbred (Duroc × Yorkshire) sows.…”
Section: Discussionmentioning
confidence: 99%
“…The impaired claw quality has been shown to have significant negative impact on longevity, productive performance and welfare of sows [ 4 , 5 , 6 , 7 , 8 ]. The increased awareness of claw quality importance in sow breeding herds has guided researchers to focus on studying the frequency and severity of hoof growth abnormalities and lesions [ 8 , 9 , 10 , 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%